Comparison of antimicrobial efficacy and therapeutic index properties for common wound cleansing solutions, focusing on solutions containing PHMB - Watson, Fergus; Chen, Rui; Saint Bezard, Jeanne; Percival, Steven (GMS Hygiene and Infection Control)
Background: Surgical site infections (SSIs) have been shown to increase patient morbidity and mortality, impact on quality of life and place a significant economic burden on healthcare systems worldwide. Irrigation using wound cleansing and antiseptic effective solutions during surgical procedures is a key part of SSI prevention. The optimal solution would have minimal cytotoxicity to the patient while maintaining a minimum concentration required for antimicrobial activity necessary to prevent opportunistic pathogens and biofilm formation.Method: A variety of common wound irrigation products, including polyhexanide in various concentrations and compositions, iodine and hypochlorous acid-based solutions, were tested and compared for their activity against pathogens according to the ESKAPE group of nosocomial relevant microbes. The antimicrobial efficacy of the solutions was tested against planktonic cells using a time-kill assay. Its minimal bactericidal concentration (MBC) and its cytotoxicity against mouse fibroblast cells were determined. Finally, the Therapeutic Index (TI) was compared and the biofilm activity of a selected solution containing 0.1% polyhexanide (PHMB) was tested. Results: Irrigation solutions containing 0.1% PHMB demonstrated rapid inactivation against planktonic cultures, achieving >4 lg reduction within 60 seconds. When comparing the TI of all irrigation solutions tested, the combination of 0.1% PHMB and poloxamer as an additive showed the best results in killing nosocomial pathogens and also to be less cytotoxic to mammalian fibroblasts, as demonstrated for Surgical Irrigation. When exposed to five single-species biofilms, PREVENTIA Surgical Irrigation showed a 3 lg reduction (average) after 60 minutes; this was supported by microscopy showing significant biofilm disruption and an abundance of non-viable microcolony formations.Conclusion: This study highlights the impact of irrigation solutions containing PHMB. It also demonstrated the effect of using different concentrations of PHMB in combination with surfactants as additives. The combination of 0.1% PHMB and poloxamer as a surfactant demonstrated effective benefits in eradicating established biofilm combined with a relatively high Therapeutic Index (TI), indicating low cytotoxicity and high bactericidal activity.